Evolution during refrigerated storage of bioactive compounds and quality characteristics of grapefruit [Citrus paradisi (Macf.)] juice treated with UV-C light - la Cava, Enzo Luciano Marcelo (2015)
The effect of the UV-C light (doses: 0.0-3.94J/cm2) on the main bioactive compounds of grapefruit juice and their stability were evaluated throughout 30 and 16 days of storage at 4 and 10°C respectively. Organic acids (citric, malic, ascorbic and tartaric) and flavonoids (naringin, hesperidin and neohesperidin) were quantified by HPLC, whereas total phenols and the antioxidant capacity were determined by spectrophotometric methods. The UV-C treatments caused a significant decrease (15%-30%) in ascorbic acid and antioxidant capacity (10%-27%), which was related to the applied dose. However, no changes (p>0.05) in others organics acids, individual flavonoids, total phenols, pH, °Brix, color and titratable acidity were observed after UV-C treatment. During the storage at both temperatures, a decrease in the neohesperidin levels (43%-53%) was detected whereas the others parameters analyzed did not show changes (p>0.05). The microbiological quality of grapefruit juices treated with 3.94J/cm2 was maintained for 15 and 10 days at 4 and 10°C respectively.